Ang ibong lumalakad - Fast, Emily Rose 1996-
"Ang Ibong Lumalakad follows the journey of Kate, a bird mascot, on her way home for the night through the bright and busy streets of Quezon City. As she passes by the familiar sights, she attracts stares and comments from fellow commuters. While some take her in with disbelief, others attempt to understand what they see. The end of the mascot's travels brings her to her destination where she is free to reveal who she is underneath the costume. The film leans on a post-modern view of the Other wherein the Other is identified as someone who is different yet places them at the center of the conversation. It also acts as an addition to Third Culture Kid studies as the film emphasizes how one can feel at home in a place they might never fit in, as opposed to the confusion of cultures that is commonly discussed."